A intensificação do agenciamento nos games: do jogador ao jogador-criador - Zille, José Antônio Baêta (2012)
The increase of complexity and of players participation in videogames constitutes important changes in the development of videogames. When a player s universe is amplified, when players partake in a game that changes their role from players to creator-players, and when certain techniques are used to allow the player to participate more fully in a game, this trend in development can be seen. Our hypothesis is that this development is a result of the agency potential of videogames. This raises the question: how has the increase in the agency potential of such games affected players? This research focuses on the user subjects and their changes in cognition/perception and creativity, and in the increase of their subjectivity. In order to discuss in detail the concepts of interactivity, creativity, and the increase in subjectivity and the cognitive process, this study uses the concepts of agencement (Deleuze and Guattari, 1993), and of agency (Murray, 1997). Based on these discussions, aspects of a selected sample of games were analyzed, bringing to attention those aspects which confirm an increase of changes in the users as the agency is amplified. The sample of games selected for analysis was chosen by considering those whose historical development exhibited greater complexity in the agency array and a greater level of player participation; narrative characteristics were also considered. The games selected for this study were: Computer Space (1971), the first mass-produced videogame; Myst (1993), in which there is a closed interactive narrative; and The Sims 3 (2009), which plays under an open interactive narrative. Videogames can be considered to be cultural environments which yield dialogue through sign processes between the game s creators, players, and the game s own universe. It is our intent to gain a better understanding of the mechanism of this communication process. This understanding, besides contributing a better understanding of human vicissitudes, will make it possible for new knowledge to be transposed to other fields of study, and will enrich the intrinsic cultural environments of videogames